Screening of lignin degrader from soil - Noor Zanida, Zamani (2008)
Since many years ago many researches have been done in order to find the latest, cheaper and more effective ways of getting out of lignin so that they can get to the cellulose fibers. Lignin is the main problems in the pulps and paper industries. The presence of lignin makes the newsprint turn yellow. Besides that, the presence of lignin also contributed to problems such as acid gives off as the woods deteriorates. So that, in order to produce fine papers it is needed to removes the lignin. Biodegradation of lignin by microorganisms is the latest technology being found to replace the conventional method which using chemicals to remove lignin. Using microorganisms to removes lignin contributed in reducing cost and besides that, this method is really friendly to the environment. The main objectives of this study are to screen, to characterized microorganisms from soil that produce the lignin degrading enzymes and to analyze the enzyme activity. This process includes of two phases: screening process and the characterization process. Screening process was done using selective agar containing alkaline lignin. The microbe was characterized using simple staining, gram staining, and spore staining. The lignin degrading microbe found was tested; the result was a gram positive and, having endospore. The optimum pH was found to be in pH 7.0 while the optimum temperature discovered was 50°C with enzyme activity at 588.3 µmol/ml/min.